2022
DOI: 10.1177/10998004221124273
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Gut Microbiota Associated With Depressive Symptoms and Sleep Disturbance Among Chinese and Korean Immigrants in the United States

Abstract: Context Depression is prevalent among Asian Americans (AsA) during the COVID-19 pandemic, and depression often leads to sleep disturbance in this population. The gut microbiota (GM) plays a critical role in mental health and sleep quality, and the composition of the GM is largely unknown among AsA. Objectives Examine associations of the GM with depressive symptoms and sleep disturbance among Chinese and Korean American immigrants. Methods Depressive symptoms (PROMIS Short Form-Depression) and sleep quality (Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Regarding the β diversity, which is the index of microbial community compositions in different individuals, the depressed group had a more minor inter-individual difference than the non-depressed group. This is consistent with previous studies indicating that microbial β diversity is associated with depressive symptoms [ 43 , 44 , 45 ]. There was no difference in beta diversity between the two groups with or without anxiety, which is similar to the review results of Nikolova VL et al [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the β diversity, which is the index of microbial community compositions in different individuals, the depressed group had a more minor inter-individual difference than the non-depressed group. This is consistent with previous studies indicating that microbial β diversity is associated with depressive symptoms [ 43 , 44 , 45 ]. There was no difference in beta diversity between the two groups with or without anxiety, which is similar to the review results of Nikolova VL et al [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Emerging evidence suggests that the microbiome, particularly the gut, plays an important role in mental health via the microbiota‐gut‐brain axis (the bidirectional communication network between the brain and gut) (Winter et al, 2018). Higher levels of depressive symptoms were associated with lower gut microbiome diversity, and higher levels of anxiety symptoms were associated with lower oral microbial diversity among first‐ and second‐generation Asian immigrants living in the U.S. (Hope et al, 2022; Richardson et al, 2023). The opposite trend was observed for the oral microbiome among Asian immigrants such that greater diversity was associated with increased depression symptoms (Richardson et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Asian immigrants with more depressive symptoms had higher abundances of Actinobacteria in their gut microbiota, while those without depressive symptoms or with mild symptoms had higher abundances of Bacteroidetes . Those with moderate/severe depressive symptoms had higher abundances of Lactobacillales (Hope et al, 2022). Trends showed that Asian immigrants with less sleep disturbance had higher abundances of Bacteroidetes and a lower abundance of Actinobacteria and Firmicutes .…”
Section: Resultsmentioning
confidence: 99%